Discovery of novel Bmy1 alleles increasing β-amylase activity in Chinese landraces and Tibetan wild barley for improvement of malting quality via MAS. - Xue Gong (Public Library of Science (PLoS), 2013)
China has a large barley germplasm collection which has not been well characterized and is therefore underutilized. The Bmy1 locus encoding the β-amylase enzyme on chromosome 4H has been well characterized in the worldwide barley germplasm collections due to its importance in the malting and brewing industry. The Bmy1 locus was chosen as an indicator to understand genetic potential for improvement of malting quality in Chinese landraces and Tibetan wild barley. The genetic diversity of 91 barley accessions was assessed using allele specific Multiplex-ready molecular markers. Eight accessions were further sequenced, based on the Multiplex-ready marker diversity for Bmy1 in the germplasm. Six of the eight accessions clustered together in a unique group, and showed similarities to 'Haruna Nijo', wild barley accession PI296896 and 'Ashqelon'. Sequence comparisons with the known Bmy1 alleles identified not only the existing 13 amino acid substitutions, but also a new substitution positioned at A387T from a Chinese landrace W127, which has the highest β-amylase activity. Two new alleles/haplotypes namely Bmy1-Sd1c and Bmy1-Sd5 were designated based on different amino acid combinations. We identified new amino acid combination of C115, D165, V233, S347 and V430 in the germplasm. The broad variation in both β-amylase activity and amino acid composition provides novel alleles for the improvement of malting quality for different brewing styles, which indicates the high potential value of the Chinese landraces and Tibetan wild barley.